Cultural Symbols Didactize Concreteness Fading in Basic Multiplication - Ali, Clement Ayarebilla (Pendidikan Matematika STKIP Kusuma Negara, 2024)
The purpose of this study is to use cultural Adinkra artifacts to present “Concreteness Fading” in the basic multiplication of one-digit and one-digit numbers. Employing a quantitative approach, the researcher adopted a one-group pretest-posttest quasi-experimental design, and randomly selected 51 participants from 300 student teachers. Data collection involved two sets of tests, analyzed in two stages through task-based transcripts and paired-sample t-tests. The first stage analyzed the tasks the student teachers solved using “Concreteness Fading”. The results revealed smooth and joyful navigations of the stages of Concreteness Fading using the Adinkra symbols. The second stage analyzed the performance of the student teachers with t-test statistics to show significant differences between the control and experimental groups. The results of one sample t-test and paired samples t-test showed that student teachers solved more problems correctly using Concreteness Fading than the conventional concrete manipulatives. Following the findings, we concluded that heavy use of only concrete objects and examples without abstracting can be detrimental to teaching mathematics. We, therefore, recommended that student teachers should always avoid rushing to symbols and symbolic manipulations of mathematics but rather align their methods, techniques, and strategies in the transition through the three stages of Concreteness Fading.